1987
DOI: 10.1016/s0006-3495(87)83403-3
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic signals from frog skeletal muscle

Abstract: Acoustic, force, and compound muscle action-potential signals were recorded simultaneously during maximal isometric twitches of frog gastrocnemius muscles. The onset of sound production occurred after the onset of muscle depolarization but before the onset of external force production. Acoustic waveforms consisted of oscillations that initially increased in amplitude, followed by decaying oscillations. The peak-to-peak acoustic amplitude increased with increasing temperature with a Q10 of 2.6 +/- 0.2 over a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
125
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(135 citation statements)
references
References 6 publications
9
125
0
1
Order By: Relevance
“…1: (i) the gross lateral movement of the contracting fibres at the beginning of contraction (MMG complex), generated by the shortening of contractile elements before the slack of the elastic-connective tissue has been fully taken up, and F has been transmitted to the tendon insertion point [15]; (ii) the subsequent vibrations at the resonance frequency of the muscle (MMG ripple), reflecting the dimensional changes of the active fibres propagating towards the muscle surface [19][20][21][22]; and (iii) the gross lateral movement of the muscle at the end of contraction (R-MMG complex), due to the maximum acceleration of muscle surface caused by cross-bridges detachment and series elastic components (SEC) detensioning [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…1: (i) the gross lateral movement of the contracting fibres at the beginning of contraction (MMG complex), generated by the shortening of contractile elements before the slack of the elastic-connective tissue has been fully taken up, and F has been transmitted to the tendon insertion point [15]; (ii) the subsequent vibrations at the resonance frequency of the muscle (MMG ripple), reflecting the dimensional changes of the active fibres propagating towards the muscle surface [19][20][21][22]; and (iii) the gross lateral movement of the muscle at the end of contraction (R-MMG complex), due to the maximum acceleration of muscle surface caused by cross-bridges detachment and series elastic components (SEC) detensioning [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…During neuromuscular tissue activation, the time lag between the onset of EMG and MMG signals (Δt EMG-MMG ) (Esposito et al, 2011) noted the existence of excitation-contraction coupling. Regarding this, Barry (1987) monitored the electrical and mechanical responses of the gastrocnemius muscle and found that the mechanical response onset occurred after muscle depolarization but before the emergence of external force production. Cabral et al (2013) measured the time lag between the onset of electrical stimulation and the onset of the mechanomyographic signal (using accelerometer) in one spinal cord injured subject and one able-bodied subject.…”
Section: Clinical Assessment and Rehabilitation Biofeedbackmentioning
confidence: 99%
“…Several researchers have attempted to eliminate or separate FT from MMG signals through the use of a Fourier truncation (Goldenberg et al, 1991) or through the use of coherence analysis (Itoh et al, 2000). Barry (1987) argued that it is necessary to remove the influence of FT from MMG signals since the FT may affect MMG signals. Thus, it is necessary to find a method to reduce or eliminate the interfusion of FT with MMG.…”
Section: ) Graduate School Of Science and Technology Chiba Universimentioning
confidence: 99%
“…However, FT (Barry, 1987;Oster and Jaffe, 1980;Itoh et al, 2000;Goldenberg et al, 1991;Orizio, 1993) and motion artifacts (Tarata, 2003;Watakabe et al, 2001) have been…”
Section: Introductionmentioning
confidence: 99%